2016
DOI: 10.1016/j.bbamcr.2016.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Aβ-Induced Drp1 phosphorylation through Akt activation promotes excessive mitochondrial fission leading to neuronal apoptosis

Abstract: Mitochondrial dysfunction is known as one of causative factors in Alzheimer's disease (AD), inducing neuronal cell death. Mitochondria regulate their functions through changing their morphology. The present work was undertaken to investigate whether Amyloid β (Aβ) affects mitochondrial morphology in neuronal cells to induce apoptosis. Aβ treatment induced not only the fragmentation of mitochondria but also neuronal apoptosis in association with an increase in caspase-9 and -3 activity. Calcium influx induced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
104
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(111 citation statements)
references
References 73 publications
6
104
0
1
Order By: Relevance
“…Cytosolic Ca 2+ has been known to play a role in mitochondrial fragmentation in some studies [56], [57]. We found that phosphorylation at the inhibitory site of DRP1 was decreased in ΔMICU1 cells, indicating increased DRP1 activity.…”
Section: Discussionmentioning
confidence: 54%
“…Cytosolic Ca 2+ has been known to play a role in mitochondrial fragmentation in some studies [56], [57]. We found that phosphorylation at the inhibitory site of DRP1 was decreased in ΔMICU1 cells, indicating increased DRP1 activity.…”
Section: Discussionmentioning
confidence: 54%
“…Manczak et al found that Drp1 interacts with Aβ monomers and oligomers in AD patients and these abnormal interactions are increased with the disease progression [26]. Dah et al reported Aβ could also activate Drp1 through sustained phosphorylation of Akt [8]. Thus, it is reasonable to suppose that Drp1-Aβ42 interaction is implicated in the regulatory mechanism of Drp1 in Aβ42 transgenic Drosophila .…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the continuous production, degradation and the aggregation of amyloid beta-protein (Aβ) lead to AD [7]. Aggregation of beta amyloid (Aβ42) and tangles of neuronal fibers are the main pathological features [8,9]. However, the mechanisms driving the disease have not been completely understood.…”
Section: Introductionmentioning
confidence: 99%
“…The second reason is that the decreased clearance of Aβ by some organelles and cellular functions such as the lysosome, proteasome, and autophagy. Hence, drugs which are capable for promoting the clearance or inhibiting the production of Aβ may be a promising therapeutic method toward AD (D. I. Kim et al, ; B. Kim, Park, Chang, & Lee, ; Lv, Yang, Cui, & Su, ; Pickett et al, ; Sarkar, Jun, & Simpkins, ; Yan et al, ).…”
Section: Drp1 and Neurodegenerative Diseasesmentioning
confidence: 99%